Segregation texts: Riksdag's open data: Interpellations - Språkbanken Text (University of Gothenburg, 2024)
Interpellations from members of the Riksdag to the government

Interpellationer från ledamöterna till regeringen
Segregationstexter: Riksdagens öppna data: Interpellation
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik